Consumer Buying Interest: Prices And Product Quality At HRVD Division Store - Irvan, Nur Fajri; Fadli M, Muhammad; Saharuddin, Saharuddin; Misi, Hasrullah Liong (Entrepreneurship Undergraduate Program at Amkop Business School, 2024)
The study, set against the backdrop of increasingly competitive business environments, aims to understand how these factors—price and product quality—affect consumer buying interest, particularly at the HRVD Division Store in Makassar City, South Sulawesi.Utilizing a quantitative research approach, the study involved consumers of the HRVD Division Store as its population, with a total sample size of 30, reflecting the entire population of interest due to its size being less than 50. Through semi-structured interviews and statistical analysis using SPSS v.26, the research delved into the influences of price and product quality on buying interest, concluding that both factors significantly impact consumer purchase decisions. The findings reveal that price significantly affects purchase interest, suggesting that consumers are sensitive to pricing strategies that match their economic conditions. Similarly, product quality was found to have a significant impact, indicating that superior quality products are more likely to attract consumer interest and potentially command premium prices. The study further concludes that both price and product quality together significantly influence consumer buying interest, highlighting the importance of balancing these factors to enhance market competitiveness and consumer satisfaction. This research contributes to the broader understanding of consumer behavior, suggesting that effective marketing strategies must consider both the price and quality of products to meet consumer expectations and foster loyalty. However, the study acknowledges limitations in its geographical scope and sample representation, recommending further research to explore these dynamics across different contexts for more generalizable insightsKeywords: Consumer Buying Interest; Price Impact Product